Palm oil biofuels demystification: The needs of standardized life cycle assessments and source derivatization - Melia Laniwati; Tirto Prakoso; Jenny Rizkiana; Anita Kusumawardhani; Haryo Pandu Winoto (Communications in Science and Technology, 2026)
The implementation of binary renewable-versus-fossil policy frameworks has the effect of obscuring the environmental costs and overstating the sustainability of palm oil biofuel. This review examines life cycle assessment (LCA) studies and regulatory frameworks, demonstrating that land-use change (LUC) is the predominant source of greenhouse gas and deforestation poses a threat to over 80% of species in production regions. Inconsistent system boundaries have been found to hinder comparability, with certification schemes including RSPO, ISPO, and EU RED II frequently overlooking LUC data, thus perpetuating unsustainable plantation strategies. As one of the most imminent solutions, used cooking oil (UCO) appears as a viable alternative, exhibiting a carbon intensity that is more than 60 % lower than that of conventional jet fuel and potentially resulting in a reduced depletion of fossil resources. However, only approximately 20% of global domestic UCO is recycled and 85% of regions lack UCO-specific legislation. A three-pillar framework is proposed: harmonized LCA with mandatory LUC accounting, scaled UCO valorization, and biodiversity-friendly practices including agroforestry and castor cultivation on degraded lands. It is reported that these measures can reduce emissions by 67.2% without compromising land integrity or food security. The notion of directly comparing the non-use of palm oil with the complete disregard for its unsustainability may be alleviated in the future by regarding some of the aspects proposed in this study.